PENGARUH CORPORATE SOCIAL RESPONSIBILITY, BEBAN PAJAK TANGGUHAN DAN TAX PLANNING TERHADAP MANAJEMEN LABA - Syamsul Asmedi; Rizky Wulandari (Perwira Journal of Economics & Business, 2021)
This study aims to examine the effect of corporate social responsibility, deferred tax burden and tax planning on earnings management. The independent variables used in this study are corporate social responsibility, deferred tax burden and tax planning, while the dependent variable in this study is earnings management. The type of research used in this research is quantitative data. Sources of data used in this study is secondary data. The population in this study are manufacturing companies in the consumer goods and industrial sector listed on the Indonesia Stock Exchange (IDX) during the 2014-2018 period. Determination of the sample of this study using purposive sampling method and obtained a research sample of 10 companies. Analysis of the data used in this study is descriptive statistical test, classical assumption test and hypothesis testing. The analytical method used is a hypothesis with the help of SPSS version 25 software. The results of this study indicate that corporate social responsibility has no significant effect on earnings management, deferred tax expense has no significant effect on earnings management and tax planning has a significant effect on earnings management. Meanwhile, simultaneously shows that corporate social responsibility, deferred tax expense and tax planning together have a significant effect on earnings management. Keywords: Corporate Social Responsibility, Deferred Tax Burden, Tax Planning, Earnings Management.